A dynamic energy-based model to analyze sublethal effects of chronic gamma irradiation in the nematode Caenorhabditis elegans. Issue 16 (17th September 2017) - Lecomte-Pradines, Catherine; Hertel-Aas, Turid; Coutris, Claire; Gilbin, Rodolphe; Oughton, Deborah; Alonzo, Frédéric
ABSTRACT: Understanding how toxic contaminants affect wildlife species at various levels of biological organization (subcellular, histological, physiological, organism, and population levels) is a major research goal in both ecotoxicology and radioecology. A mechanistic understanding of the links between different observed perturbations is necessary to predict the consequences for survival, growth, and reproduction, which are critical for population dynamics. In this context, experimental and modeling studies were conducted using the nematode Caenorhabditis elegans . A chronic exposure to external gamma radiation was conducted under controlled conditions. Results showed that somatic growth and reproduction were reduced with increasing dose rate. Modeling was used to investigate whether radiation effects might be assessed using a mechanistic model based upon the dynamic energy budget (DEB) theory. A DEB theory in toxicology (DEB-tox), specially adapted to the case of gamma radiation, was developed. Modelling results demonstrated the suitability of DEB-tox for the analysis of radiotoxicity and suggested that external gamma radiation predominantly induced a direct reduction in reproductive capacity in C. elegans and produced an increase in costs for growth and maturation, resulting in a delay in growth and spawning observed at the highest tested dose rate.